Ticagrelor Conditioning Effects Are Not Additive to Cardioprotection Induced by Direct NLRP3 Inflammasome Inhibition: Role of RISK, NLRP3, and Redox Cascades. (4th August 2020) - Penna, Claudia; Aragno, Manuela; Cento, Alessia Sofia; Femminò, Saveria; Russo, Isabella; Bello, Federica Dal; Chiazza, Fausto; Collotta, Debora; Alves, Gustavo Ferreira; Bertinaria, Massimo; Zicola, Elisa; Mercurio, Valentina; et al.
Abstract : Inhibition of either P2Y12 receptor or the nucleotide-binding oligomerization domain- (NOD-) like receptor pyrin domain containing 3 (NLRP3) inflammasome provides cardioprotective effects. Here, we investigate whether direct NLRP3 inflammasome inhibition exerts additive effects on myocardial protection induced by the P2Y12 receptor antagonist Ticagrelor. Ticagrelor (150 mg/kg) was orally administered to rats for three consecutive days. Then, isolated hearts underwent an ischemia/reperfusion (30 min ischemia/60 min reperfusion; IR) protocol. The selective NLRP3 inflammasome inhibitor INF (50 μ M) was infused before the IR protocol to the hearts from untreated animals or pretreated with Ticagrelor. In parallel experiments, the hearts isolated from untreated animals were perfused with Ticagrelor (3.70 μ M) before ischemia and subjected to IR. The hearts of animals pretreated with Ticagrelor showed a significantly reduced infarct size (IS, 49 ± 3 % of area at risk, AAR) when compared to control IR group (69 ± 2 % of AAR). Similarly, ex vivo administration of INF before the IR injury resulted in significant IS reduction (38 ± 3 % of AAR). Myocardial IR induced the NLRP3 inflammasome complex formation, which was attenuated by either INF pretreatment ex vivo, or by repeated oral treatment with Ticagrelor. The beneficial effects induced by either treatment were associated with the protective Reperfusion Injury Salvage Kinase (RISK) pathway activation and redox defence upregulation. In contrast, no protective effects nor NLRP3/RISK modulation were recorded when Ticagrelor was administered before ischemia in isolated heart, indicating that Ticagrelor direct target is not in the myocardium. Our results confirm that Ticagrelor conditioning effects are likely mediated through platelets, but are not additives to the ones achieved by directly inhibiting NLRP3.